ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK BADAN (Studi Empiris pada Perusahaan Industri yang Terdaftar di Kantor Pelayanan Pajak Pratama Tegal) - Nikoriski, 10.05.52.0180; Meita Oktaviani, Rachmawati (Students Journal of Accounting and Banking, 2014)
This Research aim to to test and analyse attitude, intention, condition of finance, company facility, and organizational climate to Tax Compliance. Population in this research is tax professional which is Taxpayer deputizing residing in Kantor Pelayanan Pajak Pratama Tegal. This research use intention of tax professional to tax compliance, condition of finance to tax compliance, company facility to tax compliance, and organizational climate to tax compliance as independent variable and Tax Compliance as dependen variable. Method election of sampel the used is purposive sampling with criterion for example professional tax which have worked in minimum company one year and have filled SPT. used Sampel counted 42 responder. Data analysis conducted by using analysis of regression linear with program of SPSS 16. Result of this research indicate that pursuant to result of conducted test as follows : Intention have an effect on positive to Tax Compliance, condition of finance have an effect on positive to Tax Compliance, company facility have an effect on negativity to Tax Compliance and organizational climate have an effect on positive to Tax Compliance. Keywords: intention of tax professional to Tax Compliance, condition of finance, company fasilits, organizational climate, compliance of body Iease